Body composition: a crucial factor in downstaging and postoperative complications of neoadjuvant chemotherapy for gastric cancer - Jin, Zhuanmei; Chen, Min; Yang, Qinglin; Yao, Changyu; Li, Yanting; Zhang, Taohua; Lai, Min; Li, Shuangxi; Ding, Lipeng; Yuan, Wenzhen (Frontiers in Nutrition, 2024)
Background In our previous investigations, we observed no significant difference in OS among patients who underwent neoadjuvant chemotherapy (NAC), regardless of complications. We propose that for patients who underwent reoperation following NAC, downstaging (reduction of clinical stage) and postoperative complications exerted contrasting effects on the OS. Further, we hypothesize that post-NAC downstaging and the absence of postoperative complications lead to a longer OS. Methods We conducted a retrospective analysis to collect the clinical data of patients with GC who underwent surgery after receiving NAC at the First Hospital of Lanzhou University from January 2016 to December 2022. Based on the presence of a post-NAC downstaging period and postoperative complications, we categorized the patients into group A(downstaging without complications), group B(downstaging with complications), group C(non-downstaging with complications), and group D(non-downstaging without complications). First, we assessed the OS disparity between the groups. Subsequently, we performed a comparative analysis of the body composition and hematological indexes of patients from the four groups. Results Group A comprised 83 patients(28.1%), group B comprised 32 patients(10.8%), group C comprised 83 patients(28.1%), and group D comprised 97 patients(32.9%). Group A patients had the longest OS of 40.1 ± 20.53, whereas group C patients had the shortest OS of 32.15 ± 25.09. Pairwise comparisons revealed significant differences between the OS of group A patients and that of group C(32.15±25.09) and D(33.06±20.89) patients(P<0.05). The skeletal mass index (SMI) and skeletal mass area (SMA) were highest in group A, lowest in group C, higher in group A(SMI: 45.05±7.44, SMA: 128.88±22.67) than in group C(SMI: 41.61±8.17, SMA: 115.56±26.67) (p<0.05), and higher in group D(SMI: 44.94±6.87, SMA: 127.05±23.09) than in group C(p<0.05). With respect to hematological indexes, the prognostic nutritional index (PNI) was highest in group A and lowest in group C. The PNI in group A(417.89±37.58) was significantly higher than that in group C(397.62±47.56) (p<0.05), and it was also higher in group D(410.76±4.28) than in group C(p<0.05). Conclusion Patients with advanced GC who experienced post-NAC downstaging and no postoperative complication had the longest OS. Patients with better body composition demonstrated more significant downstaging, fewer postoperative complications, and a longer OS.